Digital liaisons: Connecting diverse voices to support an ethical and sustainable information future in digital libraries. Issue 1 (1st February 2019) - Grguric, Ekatarina; Khan, Nushrat; Gamble, Alyson; Hockin, Tamarack; Dressler, Virginia
ABSTRACT: Digital Liaisons is a platform for including student and early career voices in open dialogue with practitioners and researchers who work in or adjacent to the field of Digital Libraries. It has taken several forms over the last few years, ranging from a poster session, to an unconference‐style panel, to moderated Twitter chats. This year we are proposing to merge two of these approaches: a series of Twitter chats that provide mentor‐mentee connections for early career practitioners, and a panel which reports on the outcomes of these chats and concludes with a digital poster session for students and early‐career practitioners. The merger of Twitter chats and a digital poster session will provide two ways for participants to interact with the theme of this year's conference and will allow sharing their views and experiences.